PENGARUH PEMBERIAN KITOSAN TERHADAP PENYAKIT ANTRAKNOSA PADA TANAMAN CABAI (Capsicuum annuum L.) - Hariman, Hariman; Suswanto, Iman; Ruliyansyah, Agus (Jurnal Sains Pertanian Equator, 2025)
This study aims to test the effectiveness of chitosan compounds in controlling anthracnose disease (Colletotrichum capsici) on large chili plants (Red pepperL.). The study was conducted in September 2022-January 2023 for 4 months at Jl. Purnajaya 1, Siantan Hilir District, Kota. The study used a Completely Randomized Design with 6 levels of treatment doses, namely 0.05% chitosan, 0.10% chitosan, 0.15% chitosan, 0.20% chitosan, a negative control without treatment, and a positive control in the form of propineb 70% 2 g/l. The variables observed were disease incidence and disease severity after application of various treatment concentration levels. Data analysis used analysis of variance in the Minitab v.19 program. The results showed that the treatment of chitosan compounds on the development of anthracnose disease in the field test had no significant effect on the variables of disease incidence, disease severity, AUDPC calculations and regression. It is suspected that the absence of the effect of chitosan compounds in suppressing the development of anthracnose disease is due to the concentration given being too low so that the chitosan compound does not work effectively in protecting chili fruit